Influence of Schooling and Age on Cognitive Tests - Juliana Lima Quintas; Einstein Francisco Camargos; Cláudia Velloso Silva Melo; Otávio Toledo Nóbrega (Brazilian Society of Geriatrics and Gerontology, 2024)
OBJECTIVES: To identify factors that interfere with performance in cognitive tests frequently used for non-demented elderly in clinical practice. METHOD: Sample composed of 213 individuals, mean age 72.9 ± 6.1 years. The following assessment instruments were applied: Geriatric Depression Scale; Mini-Mental State Examination (MMSE); Verbal Paired Associates tests I and II (VPA) from the Wechsler Memory Scale (WMS); Direct and Reverse Order Wechsler Adult Intelligence Scale-III (WAIS-III); Simple Reaction Time (SRT), and Tower of Hanoi. A multiple linear regression model was used to verify interaction between dependent and independent variables. RESULTS: For the most part, the tests were not significantly influenced when adjusted for gender, marital status, depressive symptoms or use of psychotropic drugs. Significant interference of schooling and age on performance in applied cognitive tests was pointed out. There was a high correlation between MMSE scores and schooling, with a 1-point increase in the value obtained in the test for every four years of schooling (p < 0.0001). Results of short-and long-term memory tests were also significantly influenced by schooling (p = 0.0001, p = 0.02, respectively). Low schooling had a negative influence on attention performance according to SRT, significantly increasing reaction time (p = 0.002), error percentage (p = 0.01) and proportion of false alarms (p = 0.01). CONCLUSION: Our study found out a significant influence of age and schooling on performance of non-demented elderly in cognitive tests assessing overall performance, short- and long-term memory, attention, cognitive flexibility, and processing speed.